Application of data mining in e-business and finance [electronic resource] / edited by Carlos Soares, ... [et al.]. - Soares, Carlos A. Mota, 1945-
Đầu trang nhan đề:Contains extended versions of a selection of papers presented at the workshop Data mining for business, held in 2007 together with the 11th Pacific-Asia Conference on Knowledge Discovery and Data Mining, Nanjing China--Preface.